The Association Between Incorrect Use of Antibiotic Prophylaxis and in-Hospital Surgical Site Infections – A Prospective Observational Study - Tefera, Gosaye Mekonen (Infect Drug Resist, 2020)
BACKGROUND: Surgical site infection (SSI) is the most prevalent in developing countries where 61–90% of cases develop in-hospital. The study aimed to assess the correctness of antibiotic prophylaxis (AP) use, the incidence of in-hospital SSI, and its determinants. PATIENTS AND METHODS: A 3-month hospital-based prospective observational study design was used on general surgery patients. The criteria for identification of SSI were performed based on the Center for Disease Control and Prevention’s (CDC’s) definition of SSI. The correctness of AP was performed based on the American Society of Health System Pharmacist 2013 guideline (ASHP). Multiple stepwise backward logistic regression analysis was used at p-value <0.05 to predict SSI. RESULTS: Of 269 adult patients, the type of admission was almost equal between emergency and elective surgery. The mean (± SD) age of the study participants was 41.95±17.764. Only 19.7% of the study participants used AP correctly. The incidence rate of in-hospital SSI was 16.7% (45/269), which corresponds to 45/4736 or 9.5/1000 person-days. Independent predictors for SSI were American Society of Anesthesiology (ASA) class III–IV (p-value <0.0001), patients with age-adjusted Charlson co-morbidity index (CCI) of ≥1 score (p value=0.008), and incorrect use of AP (p-value =0.025). CONCLUSION: Incorrect antibiotic prophylaxis use contributed to an increased risk of SSI, which needs urgent attention in the present study area.